Dimensi Sosial dalam Community Based Tourism (CBT): (Studi Pada Destinasi Wisata Nefo Kaenka, Desa Fatukoto Kabupaten TTS) - Grace Oni Oet Neolaka; Hendrik Toda; Mariayani O. Rene; Lurensius P. Sayrani (Dharma Ekonomi, 2024)
Community Based Tourism (CBT) is one of the approaches in tourism development. The Community Based Tourism approach can be viewed from several dimensions, namely dimensions; economic, social, cultural, political. This study aims to analyze the social dimension in Community Based Tourism (CBT) in Fatukoto Village, Timor Tengah Sekatan Regency, with a focus on community involvement, development of community pride, and improving the quality of life of local communities. This research uses a qualitative approach, data collection using interview techniques, observation and literature study. The data collected consisted of primary data obtained through interviews and observations, and secondary data obtained from documents in the village office and the management group. The collected data were then processed and analyzed. The results showed that the management and development of tourist destinations. The results showed that the active participation of the community, pride in local culture, and an increase in the quality of life of the community were key factors in the success of community-based tourism in Fatukoto village. But on the other hand, the income received by the community is still considered low because the existing jobs are still micro and medium enterprises and the income of the community is still considered low.